PERAN GENDER DALAM MEMODERASI PENGARUH PERCEIVED BENEFIT DAN PERCEIVED COST TERHADAP NIAT MENGGUNAKAN ASURANSI JIWA DI KOTA DENPASAR - Sari, Lidya Ratna; Kusumadewi, Ni Made Wulandari (E-Jurnal Manajemen, 2015)
This research was conducted in the city of Denpasar on the basis that the city of Denpasar is the capital of the province with a large population. The number of samples taken are as many as 100 people, use of non-probability sampling technique with purposive sampling method. Data was collected through questionnaires. Technical analysis of the data used is Moderated Regression Analysis (MRA). The results of this study indicate that the perceived benefits result positive and significant effect on the intention to use. It shows that the perception of the benefits of supporting the formation of intent to use. Perceived cost a significant negative effect on the intention to use. It shows that when the perceived cost of decreasing the intention of using insurance increases. Gender did not moderate the effect of the perceived benefits to the intention of using life insurance. This resulted in the perceived influence on the intention to use the insurance benefits decline. Gender did not moderate the perceived influence on the intention to use the cost of life insurance, this resulted in the intention of using life insurance increased
Keywords: perceived benefits, perceived cost, gender, use of consumer intentions